Granulomatous inflammation in ginbuna crucian carp Carassius auratus langsdorfii against Mycobacterium gordonae. (February 2019) - Kato, Goshi; Kakazu, Taichi; Yamada, Mitsuo; Lau, Lik-ming; Nakajima, Kazue; Sato, Shoh; Nakanishi, Teruyuki; Endo, Makoto; Sano, Motohiko
Abstract: In this study, we investigated the immune responses against Mycobacterium gordonae in ginbuna crucian carp. Cumulative mortality of ginbuna injected with 2.0 × 10 7 CFU of M. gordonae was 50% at 170 days post-infection. CD4-1, CD8α, T-bet and IFNγ2 gene expression levels were significantly upregulated in ginbuna injected with 1.9 × 10 8 CFU of M. gordonae at 21 and 28 days post-infection. The CD4-2 level did not change during the experiment. Granulomatous responses consisted of central macrophage accumulation and surrounding lymphocytes, and Ziehl-Neelsen-positive bacteria were observed in the trunk kidney of the challenged fish. Immunohistochemistry using anti-ginbuna IFNγs and anti-ginbuna CD4-1 polyclonal antibody revealed that the marginal lymphocytes were positive for CD4-1, and the IFNγ-producing cells surrounded the mycobacterial cell-laden phagocytes. These results suggest that CD4-1 + cells and IFNγ2 play important roles in the granulomatous inflammation against Mycobacterial infections in teleosts. Highlights: Granulomas were observed in the trunk kidney of M. gordonae challenged fish. CD4-1, CD8α and IFNγ2 levels were upregulated in the trunk kidney of challenged fish. The marginal lymphocytes in the granuloma were positive for CD4-1 molecule. IFNγ + cells surrounded the mycobacterial cell-laden phagocytes in the granuloma. CD4-1 + cells and IFNγ + cells play important roles in the granulomatous inflammation.